Identification of GyrA mutations conferring fluoroquinolone resistance in Salmonella isolated from poultry and swine from Ogun and Oyo State, Nigeria (2011)
The quinolone-resistancc determining-region of gyrA was PCR-amplified and sequenced in eight fluoroquinolone-resistant Salmonella (lcvofloxacin MICs ranging from 32-64 pg /tnL) isolated from apparently healthy swine (n=2 isolates) and poultry (n=6 isolates) that died of septicacmic clinical diseases in Ogun and Oyo State, Nigeria. All of the eight isolates possessed the gyrA mutation encoding the histidine=>tyrosine conversion at amino acid 150 (150His=>Tyr). Additional substitutions included: 83Tyr=>Ser in one Salmonella enterica serotype Give isolate (pig), 87Asp=>Tyr in one Salmonella enterica serotype Kentucky isolate (pig); 83Tyr=>Phe in one isolate characterized as 9,12:Nonmotile (poultry); and 87Asp=>Gly in three poultry' isolates including Salmonella enterica serotypes Kentucky (n=2), and Ituri (n=l). The 150His=>Tyr is novel while the other mutations have been previously reported in Salmonella spp. This is the first study to associate gyrA mutations with fluoroquinolone resistance in Nigeria, where fluoroquinolone use in livestock is not tightly regulated